STRATEGIES IN READING ONLINE TEXTS BY THAI UNIVERSITY STUDENTS: Received: 18th September 2021; Revised: 08th February 2022, 17th March 2022, 07th April 2022; Accepted: 11th April 2022 - Toomnan, Parichart (PEOPLE: International Journal of Social Sciences, 2022)
This present study aimed to scrutinize students’ use of reading strategies and to explore their reading strategy use according to their enjoyment of English learning. Mokhtari and Reichard’s (2002) reading strategies questionnaire was adapted and used to collect data from 112 undergraduates (freshmen, sophomores, and juniors) in the academic year 2021. Analysis of Variance (ANOVA) and the Chi-square tests were used to analyze data. Findings showed that students’ enjoyment of English learning affected their reading strategy use. Learners who enjoyed learning English used more reading strategies than those who had less enjoyment of English learning. It was also found that among the strategies used, Problem-solving strategies (PROB) were most frequently used followed by Support strategies (SUP) and Global reading strategies (GLOB). At the individual level of reading strategy use, students who enjoyed learning English tended to use more strategies than those who enjoyed it less.